Causality Between FDI, GNI, and Exports : Empirical Evidence from India - Yoganandan, G.; Vasan, M. (Indian Journal of Finance, 2022)
This study examined the causal relationship between India’s FDI inflows, GNI, and exports and its trend during the pre and post-liberalized eras. We conducted this study based on the time -series data extracted from the World Bank database covering a period of 5 decades starting from 1970 – 2019. The study used time-series-based econometric analysis through EViews software. Johansen’s cointegration and Granger causality tests were applied to identify the long-run connection and causality direction. The results of the cointegration test proved the existence of a causal relationship between FDI, GNI, and exports. The Granger causality test results indicated a bi -directional relationship between FDI, GNI, and exports. The results of this study provided new insights into FDI inflows and GNI. In addition, the outcomes of this study provided vigorous theoretical and managerial implications.